Proteomic profiling following immunoaffinity capture of HDL: Association of acute phase proteins and complement factors with pro-inflammatory HDL in Rheumatoid Arthritis - Watanabe, Junji (2012)
OBJECTIVE: To utilize proteomic analysis to identify protein biomarkers associated with pro-inflammatory HDL in patients with active rheumatoid arthritis. METHODS: Liquid chromatography-mass spectrometry (LC-MS) was used to analyze proteins associated with immunoaffinity purified HDL from plasma of two sets of RA patients carrying distinct HDL (anti- or pro-) inflammatory properties. Proteins were fractionated by Offgel electrophoresis and analyzed by LC-MS/MS equipped with a high capacity high performance liquid chromatography chip (HPLC-Chip) incorporating C18 reverse phase trapping and analytical columns. Sandwich enzyme-linked immunosorbent assays were used to validate select HDL-associated proteins in a second RA cohort. RESULTS: Seventy-eight proteins were identified in the HDL complexes. Twelve proteins were significantly increased in RA patients with pro-inflammatory HDL compared to RA patients with anti-inflammatory HDL. These proteins included acute phase proteins, including apolipoprotein J, fibrinogen, haptoglobin, serum amyloid A, and complement factors (B, C3, C9). Four of the proteins associated with HDL were validated in a second RA cohort. CONCLUSION: Pro-inflammatory HDL in patients with RA contains a significantly altered proteome including increased amounts of acute phase proteins and proteins involved in the complement cascade. These findings suggest that HDL is significantly altered in the setting of chronic inflammation from active RA with resultant loss of its anti-inflammatory function. The characterization of the biomarkers reported here may identify novel molecular connections that contribute to the higher risk of CVD in RA patients.